Prevalence and relationship of hypertriglyceridaemic–waist phenotype and type 2 diabetes mellitus among a rural adult Chinese population. Issue 8 (8th March 2019) - Ren, Yong-Cheng; Liu, Yu; Sun, Xi-Zhuo; Wang, Bing-Yuan; Liu, Yi; Ni, Hu; Zhao, Yang; Liu, Dechen; Liu, Xuejiao; Zhang, Dongdong; Liu, Feiyan; Cheng, Cheng; et al.
Abstract: Objective: Limited information is available on the prevalence and effect of hypertriglyceridaemic–waist (HTGW) phenotype on the risk of type 2 diabetes mellitus (T2DM) in rural populations. Design: In the present cross-sectional study, we investigated the prevalence of the HTGW phenotype and T2DM and the strength of their association among rural adults in China. Setting: HTGW was defined as TAG >1·7 mmol/l and waist circumference (WC) ≥90 cm for males and ≥80 cm for females. Logistic regression analysis yielded adjusted odds ratios (aOR) relating risk of T2DM with HTGW. Participants: Adults ( n 12 345) aged 22·83–92·58 years were recruited from July to August of 2013 and July to August of 2014 from a rural area of Henan Province in China. Results: The prevalence of HTGW and T2DM was 23·71 % (males: 15·35 %; females: 28·88 %) and 11·79 % (males: 11·15 %; females: 12·18 %), respectively. After adjustment for sex, age, smoking, alcohol drinking, blood pressure, physical activity and diabetic family history, the risk of T2DM (aOR; 95 % CI) was increased with HTGW ( v . normal TAG and WC: 3·23; CI 2·53, 4·13; males: 3·37; 2·30, 4·92; females: 3·41; 2·39, 4·85). The risk of T2DM with BMI≥28·0 kg/m 2, simple enlarged WC and simple disorders of lipid metabolism showed an increasing tendency (aOR=1·31, 1·75 and 2·32). Conclusions: The prevalence of HTGW and T2DM has reached an alarming level among rural Chinese people, and HTGW is a significant risk factor for T2DM.